(untitled) (Al-Academy, 2015)
the Research problem entitled: (compound shapes in the work of the artist Max Ernst and Ali Najjar) the nature of the concept of compound shapes and mechanisms of functioning in contemporary art done. The research consisted of(4) four parts: the first part is dealing with the methodological framework of the Search represented the research problem , which is manifested through this study to reveal the technical features of the composite shapes, that linked achievement both artists (Max Ernst) and (Ali Al Najjar). Which is crystallized into two objectives as follows: 1 - Detection of the technical features of the composite shapes in the work of Max Ernst and Ali Al-Najjar.2 - Detection of similarities and differences in the recruitment of compound shapes when Max Ernst and Ali Al-Najjar.The second chapter, represented the theoretical framework, it contained three sections Investigation Section I: Introduction of historical composite shapes in the artwork. The second topic: compound shapes in the work of the artist Max Ernst. The third topic: the compound objects in the work of artist Ali al-Najjar.The third chapter has singled out the search procedures, represented by the applications of compound shapes in a sample Alphand Max Ernst and Ali al-Najjar, and then ensure the identification of the research community and appointed by the (4) models, and then search tool and sample analysis.The fourth chapter has included the results of research and the researcher has reached conclusions to a number of results answer the goals of research, including:* Similarities in the recruitment of compound shapes in the work (Max Ernst) and (Ali Al Najjar).1 – Humanity shapes the vehicle body cubic abstract sample (1) for Ernst and (3) to (Ali Al Najjar).2 - reduction of the composite shape abstract way the sample (2) to (Ernest) and (2) for Ali Al-Najjar.* Attributes the difference in the recruitment of compound shapes in the work of Max Ernst and the carpenter.1 charm innocence and its thick permafrost fantasy world enjoyed by the dreamy compound shapes when Ali al-Najjar, the sample (2) we find different when Max Ernst beings the vehicle associated with the meanings and connotations broadcast a sense of aggressiveness, rebellion and cynicism and desire for revenge of the sample (2.1).4 - stability and calm clear of complex shapes in the sample (2) When Ali al-Najjar. While we find when Max Ernst bold, powerful and unstable sample (1).This researcher reached to a set of conclusions and then the list of sources and references.